2021
DOI: 10.1097/cu9.0000000000000030
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of wearable activity trackers in cystectomy patients to monitor for postoperative complications

Abstract: Background: To determine the feasibility of using wearables in patients undergoing radical cystectomy to monitor postoperative heart rate and activity and attempt to correlate these factors to complications and readmissions. Materials and methods: We conducted a prospective study of 20 patients undergoing radical cystectomy for bladder cancer between June 2017 and March 2018. Each patient was provided with a Garmin Vívofit heart rate (HR) activity tracker and instructed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…A study by Slade et al published last year using a similar approach, albeit with telephone rather than app-based surveys, found associations between higher step counts (activity) and a lower risk of postoperative complication following cystectomy. 1 In the colorectal literature, similar findings were noted regarding 30-day readmission when assessed in the first postoperative days after surgery, prior to discharge, and relative to baseline activity status. 2 Interestingly, another study utilizing machine learning with preoperative activity levels and patient characteristics outperformed the American College of Surgeons National Surgical Quality Improvement Program surgical risk calculator in predicting outcomes of pancreatectomy.…”
supporting
confidence: 64%
“…A study by Slade et al published last year using a similar approach, albeit with telephone rather than app-based surveys, found associations between higher step counts (activity) and a lower risk of postoperative complication following cystectomy. 1 In the colorectal literature, similar findings were noted regarding 30-day readmission when assessed in the first postoperative days after surgery, prior to discharge, and relative to baseline activity status. 2 Interestingly, another study utilizing machine learning with preoperative activity levels and patient characteristics outperformed the American College of Surgeons National Surgical Quality Improvement Program surgical risk calculator in predicting outcomes of pancreatectomy.…”
supporting
confidence: 64%
“…Technical issues such as connectivity problems and software bugs can impede the administration of care [22]. A significant portion of the available data on wearable medical devices comes from experimental studies or limited patient trials [34]. This limited pool of data makes it difficult to evaluate various performance issues, such as motion errors and sensor placement-dependent accuracy of device functionality [26 ▪▪ ].…”
Section: Discussionmentioning
confidence: 99%
“…PAM successfully captured perioperative biophysical parameters and was correlated with high patient satisfaction. Slade et al [34] evaluated the viability of using wearable devices in patients undergoing radical cystectomy to monitor postoperative heart rate and activity. According to the results, monitoring postoperative activity and heart rate in cystectomy patients was feasible, despite the fact that current wearables are not ideally suitable for this task.…”
Section: Wearable Technology In Urologymentioning
confidence: 99%
“… 147 In addition, wearable devices capture physical activity data in continuous, real-time, free-living settings without interrupting participants’ day-to-day. 11 , 17 , 18 , 21-23 , 25 , 40 , 44 , 45 , 51 , 62 , 63 , 66 , 76 , 83 , 85 , 86 , 89 , 90 , 92 , 104 , 108 , 111 , 112 , 119 , 122 , 126 , 128 , 129 , 136 , 139 , 142 , 143 , 147 , 157 , 158 , 161 , 163 , 166 , 172 , 173 , 176-178 , 181 , 188 , 192 , 194 , 208 Of the studies that reported on the adherence of wearable devices, 43 (70%) of them cited high adherence at greater than 80%. Additionally, feasibility studies generally noted positive experience/satisfaction using wearable devices, citing ease of use, comfort, usefulness, and no interference with daily activity related to Fitbits, ActivPal, and Biovotion AG devices.…”
Section: Discussionmentioning
confidence: 99%